2020
DOI: 10.1093/jiel/jgaa029
|View full text |Cite
|
Sign up to set email alerts
|

China’s ‘Going Global’ Policy: Transnational Production Subsidies Under the WTO SCM Agreement

Abstract: As China is increasingly ‘going global’, foreign direct investment under its Belt and Road Initiative is becoming heavily scrutinized. One of the concerns is that Chinese companies establishing themselves in third countries would be unfairly advantaged by the financing they receive under China’s expansionist strategy. This financing gives rise to a situation that had long been described as ‘unrealistic’, in which a government subsidizes a firm outside of its territory. When such a firm’s products are exported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the context of the BRI and increasingly unregulated official export financing, this scenario of "transnational subsidies" may become more common. 93 The way forward 2 This section outlines priority issues for intergovernmental discussion in the near and long term.…”
Section: Areas Of Debatementioning
confidence: 99%
“…In the context of the BRI and increasingly unregulated official export financing, this scenario of "transnational subsidies" may become more common. 93 The way forward 2 This section outlines priority issues for intergovernmental discussion in the near and long term.…”
Section: Areas Of Debatementioning
confidence: 99%
“…In other instances, there are simply no international trade rules to govern such contributions. 95 Scholars have opined that China is not setting up a completely new model, but is only impersonating and repurposing Western laws, since it borrows heavily from them. 96 The novelty in the Chinese model is its focus on coordination rather than strict commitment.…”
Section: China's Belt and Road Initiative: A Shift Towards Soft Lawmentioning
confidence: 99%
“…Existing studies have analyzed the social and economic effects of China's BRI from a macroeconomic perspective, such as international trade in goods, foreign investment, and industrial integration [6][7][8]. Enterprises are the ultimate vehicle for the implementation of China's BRI, so existing studies have considered related issues such as investment risk and financing constraints [9,10]. ese studies suggested that BRI will (i) help reduce the investment risks of companies investing in Belt and Road countries, (ii) ease the pressure of financial constraints, (iii) improve the level of corporate innovation, and (iv) help Chinese companies achieve the goal of industrial transformation and upgrading.…”
Section: Introductionmentioning
confidence: 99%